Delayed emergency myelopoiesis following polymicrobial sepsis in neonates. Issue 4 (May 2015) - Cuenca, Alex G; Cuenca, Angela L; Gentile, Lori F; Efron, Philip A; Islam, Saleem; Moldawer, Lyle L; Kays, David W; Larson, Shawn D
Neonates have increased susceptibility to infection, which leads to increased mortality. Whether or not this as a result of implicit deficits in neonatal innate immune function or recapitulation of innate immune effector cell populations following infection is unknown. Here, we examine the process of emergency myelopoiesis whereby the host repopulates peripheral myeloid cells lost following the initial infectious insult. As early inflammatory responses are often dependent upon NF-κB and type I IFN signaling, we also examined whether the absence of MyD88, TRIF or MyD88 and TRIF signaling altered the myelopoietic response in neonates to polymicrobial sepsis. Following neonatal polymicrobial septic challenge, hematopoietic stem cell (HSC) expansion in bone marrow and the spleen were both attenuated and delayed in neonates compared with adults. Similar reductions in other precursors were observed in neonates. Similar to adult studies, the expansion of progenitor stem cell populations was also seen in the absence of MyD88 and/or TRIF signaling. Overall, neonates have impaired emergency myelopoiesis in response to sepsis compared with young adults. Despite reports that this expansion may be related to TLR signaling, our data suggest that other factors may be important, as TRIF –/– and MyD88 –/– neonatal HSCs are still able to expand in response to polymicrobial neonatal sepsis.